Lives in Chinese Music - Rees, Helen, 1964- (Book collections on Project MUSE., 2009)
Until recently, most scholarly work on Chinese music in both Chinese and Western languages has focused on genres, musical structure, and general history and concepts, rather than on the musicians themselves. This volume breaks new ground by focusing on individual musicians active in different amateur and professional music scenes in mainland China, Hong Kong, and Chinese communities in Europe. Using biography to deepen understanding of Chinese music, contributors present richly contextualized portraits of rural folk singers, urban opera singers, literati, and musicians on both geographic and cultural frontiers. The topics investigated by these authors provide fresh insights into issues such as the urban-rural divide, the position of ethnic minorities within the People's Republic of China, the adaptation of performing arts to modernizing trends of the twentieth century, and the use of the arts for propaganda and commercial purposes. The social and political history of China serves as a backdrop to these discussions of music and culture, as the lives chronicled here illuminate experiences from the pre-Communist period through the Cultural Revolution to the present. Showcasing multiple facets of Chinese musical life, this collection is especially effective in taking advantage of the liberalization of mainland China that has permitted researchers to work closely with artists and to discuss the interactions of life and local and national histories in musicians' experiences.